Pedagogical potential of extracurricular physical culture and sports activities of the university - I.A. Fedotov (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify and substantiate the pedagogical potential of extracurricular physical culture and sports activities of the university in increasing the effectiveness of military-applied physical training of students. Methods and structure of the study. A pedagogical study was conducted from 2021 to 2023 at Orenburg State Pedagogical University, in which 107 graduate students, divided into control and experimental groups, took part. The pedagogical design of the extracurricular physical culture and sports educational environment of the university was considered as a universal model that provides the formation of a complex result of educational work with students of military applied orientation. In the process of extracurricular activities, a wide arsenal of physical exercises, elements of military-applied and sports training, psychological trainings were used. Results and conclusions. It is shown that the pedagogical potential of extracurricular physical culture and sports activities of the university can be successfully used to increase the effectiveness of military-applied physical training of students. The presented structural components and semantic guidelines of extracurricular physical culture and sports activities of students contributed to the formation of the motor component of the physical culture of the individual, the expansion of the communicative sphere and psychological stability in non-standard situations, providing effective comprehensive readiness for military service.